Electrolyte, lithium ion battery and electric equipment
By adding fluorinated benzene cyclic phosphate compounds and silicon carbonate compounds to the lithium-ion battery electrolyte solution, the problems of low energy density of lithium iron phosphate positive electrode material and insufficient wettability of the electrolyte solution are solved, and the battery is realized at high temperature and Efficient cycle and storage performance in low temperature environments.
Patent Information
- Application Number
- CN202411653394.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The use of lithium iron phosphate positive electrode material in lithium-ion batteries has problems such as low energy density, small tap density, and limited capacity improvement space. The electrolyte is insufficient wettability, resulting in low circulating and storage capacity of the battery in high temperature environments.
An electrolyte is provided, which contains a lithium salt, an organic solvent and an additive, wherein a fluoro-benzene cyclic phosphate compound and a silicon carbonate compound having a specific structure are added to improve the wettability and electrical conductivity of the electrolyte.
By introducing fluoro-benzene cyclic phosphate compounds and silicon carbonate compounds, the antioxidant and conductive properties of the electrolyte have been improved, and the cycling and storage performance of the battery in high and low temperature environments have been significantly improved.
Smart Images

Figure BDA0005141545580000021 
Figure BDA0005141545580000031 
Figure BDA0005141545580000032
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to an electrolyte, a lithium-ion battery and an electrical device. Background Art
[0002] In recent years, lithium-ion batteries have become the main power source for new energy vehicles. The large-scale application of lithium-ion battery electric vehicles depends largely on the driving range and safety, while the driving range depends on the capacity that the battery can provide. At present, lithium-ion battery technology still needs further breakthroughs to meet the higher application requirements of electric vehicles. The next generation of lithium-ion batteries must have the characteristics of large capacity, high specific energy, long life, and high safety, which requires lithium-ion batteries to develop in the direction of high energy density.
[0003] Lithium iron phosphate (LiFePO4) power batteries have the advantages of long cycle life, high safety, good high temperature stability and low price, which makes them widely used in commercial vehicles, logistics vehicles and low-cost passenger vehicles. However, the theoretical energy density and tap density of lithium iron phosphate materials themselves are low, and the space for capacity improvement is limited. Therefore, if the energy density of lithium iron phosphate power batteries is to be further improved, increasing the compaction density of the material is one of the effective and feasible solutions, but it puts higher requirements on the wettability of the electrolyte.
[0004] Large lattice deformation and local stress concentration in the CEI film lead to many microcracks at the crystal boundary and the cathode electrolyte interface. A large amount of electrolyte will be decomposed, and the microcrack surface will generate HF through electrolyte infiltration, which will dissolve the transition metal (TM) ions on the nickel-rich surface. The dissolved TM ions can be deposited on the negative electrode and will attack the solid electrolyte interface (SEI). In addition, the charged high-valent transition metal ions can also catalyze the oxidation reaction electrolyte decomposition and consume more active Li + , resulting in a thicker CEI film and greater interfacial impedance. In addition, the byproduct PF5 can catalyze the ring opening of ethylene carbonate (EC) to form brown carbonate polymers and CO2. The increase in gas production will cause the safety risks of the battery to rise sharply. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present application is to overcome the above-mentioned defects existing in the application of lithium iron phosphate positive electrode materials in lithium ion batteries in the prior art, thereby providing an electrolyte, a lithium ion battery and an electrical device.
[0006] To this end, this application provides the following technical solutions:
[0007] According to one aspect of the present application, an electrolyte is provided, comprising a lithium salt, an organic solvent and an additive, wherein the electrolyte further comprises a fluorinated benzene ring phosphate compound having a structure shown in formula (I):
[0008]
[0009] R1, R2, R3, and R4 independently represent at least one of halogen, substituted or unsubstituted alkyl with 1-5 carbon atoms, substituted or unsubstituted alkoxy with 1-5 carbon atoms, substituted or unsubstituted olefin with 1-5 carbon atoms, substituted or unsubstituted alkyne with 1-5 carbon atoms, cyano, isocyanate, and siloxane; or, R1 and R2 are connected to form a ring, and R3 and R4 are connected to form a ring, and the rings independently include at least one of substituted or unsubstituted carbon heterocycle and substituted or unsubstituted aromatic heterocycle; wherein the substituents in the substituted alkyl, substituted alkoxy, substituted olefin, substituted alkyne, substituted carbon heterocycle, and substituted aromatic heterocycle independently include at least one of halogen, CN, NH2, and CHO;
[0010] The fluorinated benzene ring phosphate compound accounts for 0.5% to 3% of the total mass of the electrolyte.
[0011] In some optional embodiments, the fluorinated benzene ring phosphate compound has any of the following structures:
[0012]
[0013] And / or, the fluorinated benzene ring phosphate compound accounts for 0.5% to 1% of the total mass of the electrolyte.
[0014] In some optional embodiments, the electrolyte further includes a silicon-substituted carbonate compound having a structure shown in the following formula (II):
[0015]
[0016] Wherein, R5, R6, R7, and R8 each independently represent at least one of halogen, substituted or unsubstituted alkyl with 1-5 carbon atoms, substituted or unsubstituted alkoxy with 1-5 carbon atoms, substituted or unsubstituted olefin with 1-5 carbon atoms, and substituted or unsubstituted alkynyl with 1-5 carbon atoms, wherein the substituents in the substituted alkyl, substituted alkoxy, substituted olefin, and substituted alkynyl independently include at least one of halogen, CN, NH2, and CHO.
[0017] In some optional embodiments, the silicon-substituted carbonate compound has any of the following structures:
[0018]
[0019] In some optional embodiments, the silicon-substituted carbonate compound accounts for 5% to 10% of the total mass of the electrolyte.
[0020] In some optional embodiments, the concentration of the lithium salt in the electrolyte is 0.5 to 2 mol / L, or 1 to 1.5 mol / L, calculated as lithium ions.
[0021] And / or, the additive accounts for 0.1% to 15% of the total mass of the electrolyte.
[0022] In the present application, the fluorinated benzene cyclic phosphate compound having the structure shown in formula (I) can be prepared by the laboratory itself. For example, the preparation method of the fluorinated benzene cyclic phosphate compound having the structure shown in formula (I-1) comprises the following steps:
[0023] S1, mixing pentafluorobromobenzene and triethylamine to obtain a mixed material;
[0024] S2, mixing the mixed material with iminodiphosphoryl fluoride (CAS: 38309-83-0), reacting, and post-treating to obtain a reaction product.
[0025] In some optional embodiments, in step S1, the molar ratio of pentafluorobromobenzene to triethylamine is 1:1 to 1:1.2;
[0026] and / or, in step S2, the reaction temperature is 40 to 60° C., and the reaction time is 12 to 48 h;
[0027] And / or, the molar ratio of pentafluorobromobenzene to iminodiphosphoryl fluoride is 1:1.0-1.2.
[0028] Specifically, the preparation route of the fluorinated benzene cyclic phosphate compound having the structure shown in formula (I-1) is as follows:
[0029] (1) After removing water and oxygen from the reaction device, the device is protected by nitrogen, and pentafluorobromobenzene is dissolved in an organic solvent and then added into the reaction container;
[0030] (2) adding triethylamine dropwise to the pentafluorobromobenzene solution in step (1) and stirring;
[0031] (3) dissolving iminodiphosphoryl fluoride in an organic solvent and then adding the solution dropwise to the reaction solution in step (2), heating and stirring to react, and obtaining a crude product;
[0032] (4) treating the obtained crude reaction product to obtain a finished reaction product;
[0033] In step (1), the organic solvent is a low boiling point solvent (e.g., an organic solvent having a boiling point below 80° C.), such as dichloromethane, dimethyl carbonate, benzene or toluene;
[0034] When triethylamine is added dropwise in step (2), white smoke is generated in the reaction container, and the temperature is room temperature;
[0035] The stirring reaction in step (3) is carried out under normal pressure, the reaction temperature is 40 to 60° C., and the reaction time is 12 to 36 hours;
[0036] In step (3), the molar ratio of pentafluorobromobenzene to iminodiphosphoryl fluoride is 1:1.0-1.2;
[0037] After the crude reaction product is prepared in step (4), the reaction solution is extracted with ice water, filtered, and concentrated by vacuum rotary evaporation to remove the low boiling point solvent, and then filtered to obtain a liquid substance (i.e., the compound represented by formula (I-1)).
[0038] In some optional embodiments, a trifluoromethylation reagent (such as FO2SCF2CO2Me) is used on the basis of the compound of formula (I-1) to react with a catalyst-loaded amount of CuI to generate compound (I-2) in situ;
[0039] Compound (I-3) can be prepared by adding siloxane to compound (I-1) for substitution reaction;
[0040] Compound (I-4) can be prepared by adding ethyl trifluoromethyl ether to compound (I-1) for substitution reaction;
[0041] Compound (I-5) can be prepared by adding 3-hydroxy-2-hydroxymethylpropionitrile to compound (I-1) for substitution reaction.
[0042] The specific operation steps and operation parameters of the above compound preparation process are conventional adjustments that can be made by those skilled in the art according to the reaction type, and are not specifically limited here. The above method has a simple synthesis route, is easy to operate, and is easy to control, which is conducive to subsequent promotion and application.
[0043] In the present application, the additive is a conventional additive known in the art, and the additive includes but is not limited to one or more of fluoroethylene carbonate, 1,3-propane sultone, vinylene carbonate, vinyl ethylene carbonate, vinyl sulfate, and lithium difluorophosphate. Preferably, the additive includes fluoroethylene carbonate, 1,3-propane sultone, vinylene carbonate, and lithium difluorophosphate; more preferably, the additive also includes fluoroethylene carbonate accounting for 2% of the mass of the electrolyte, 1,3-propane sultone accounting for 1.5% of the mass of the electrolyte, vinylene carbonate accounting for 1% of the mass of the electrolyte, and lithium difluorophosphate accounting for 1% of the mass of the electrolyte.
[0044] In the present application, the lithium salt is a conventional lithium salt known in the art, including but not limited to one or more of LiPF6, LiBF4, LiDFOB, LiBOB, LiDFBOP, LiPO2F2, LiSbF6, LiAsF6, LiCF3SO3, Li(CF3SO2)3C, Li(CF3SO2)2N, Li(FSO2)2N, LiC4F9SO3, LiClO4, LiAlO2, and LiAlCl4; preferably, the lithium salt is LiPF6.
[0045] In the present application, the organic solvent is a conventional solvent known in the art, including but not limited to one or more of carbonate solvents, carboxylate solvents, ether solvents, fluorinated carbonates, fluorinated carboxylates, and fluorinated ether solvents; preferably, the carbonate solvent includes but is not limited to one or more of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate, the carboxylate solvent includes but is not limited to one or more of methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, and butyl decalactone, and the ether solvent includes but is not limited to one or more of dibutyl ether, tetraethylene glycol, dimethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran. More preferably, the organic solvent contains ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate, and the three are mixed in a ratio of 35%, 30%, and 35% by mass.
[0046] According to another aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned electrolyte.
[0047] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned lithium-ion battery.
[0048] In the present application, the other components and preparation methods of the lithium-ion battery are conventional in the field. Typically, the lithium-ion battery also includes a positive electrode sheet and a negative electrode sheet, the positive electrode sheet includes a positive electrode collector and an active material layer provided on the positive electrode collector, and the positive electrode active material layer includes lithium iron phosphate; the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer provided on the negative electrode collector, and the negative electrode active material layer includes a negative electrode active material (graphite), a conductive agent, and a binder. The assembly method of the lithium-ion battery includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence to obtain a dry battery cell; injecting the electrolyte provided in the present application above into the fully dried lithium iron phosphate / graphite soft pack battery, and placing it at 45°C, forming it with a high-temperature fixture, and performing a secondary sealing process. Among them, the conductive agent, binder, etc. used in the electrode sheet are conventional in the field and are not specifically limited here.
[0049] In the present application, the lithium-ion battery can be used as a power source for the electrical equipment, or as an energy storage unit for the electrical equipment. The electrical equipment can be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0050] The technical solution of this application has the following advantages:
[0051] The electrolyte provided in the present application includes a lithium salt, an organic solvent and an additive, wherein the electrolyte also includes a fluorinated benzene ring phosphate compound having a structure shown in formula (I), and the fluorinated benzene ring phosphate compound accounts for 0.5% to 3% of the total mass of the electrolyte. In the present application, an appropriate amount of a fluorinated benzene ring phosphate compound with a specific structure can improve the circulation and storage capacity of the battery in a high temperature environment while effectively improving the wettability of the electrolyte, while improving the antioxidant capacity of the electrolyte and improving the low temperature and rate performance of the battery. Specifically, the fluorinated benzene ring phosphate compound can reduce the surface tension of the electrolyte on the surface of the active material, increase the wetting speed, and at the same time have a protective effect on the positive electrode, thereby improving the cycle performance of the battery and the conductivity of the electrolyte; by introducing a specific structure with a N-containing compound shown in formula (I) as a Lewis base to adsorb PF6 - This blocks the generation of PF5, thereby inhibiting the generation of gas during high-temperature cycling of the battery; in addition, the benzene ring in this type of compound also protects the positive electrode, establishing a highly stable interface film on the positive and negative electrodes, effectively preventing Fe 2+ The dissolution of P=O bonds improves the cycle performance of the battery; the oxygen atom in the P=O bond has a strong electronegativity and can form a strong electrostatic interaction with the cation, thereby promoting the movement of ions and improving the conductivity of the electrolyte. In addition, the presence of the P=O bond also helps to improve the stability of the electrolyte and reduce the decomposition of the electrolyte under high temperature or high pressure conditions, thereby improving the chemical stability of the electrolyte and enabling it to be used in the manufacture of high-performance lithium-ion batteries.
[0052] The electrolyte provided in the present application also includes a silicon-substituted carbonate compound having a structure shown in formula (II). The silicon-substituted carbonate compound can reduce the viscosity of the electrolyte, which is beneficial to the uniform distribution of current density and the stable formation of SEI film, further improves the low temperature and rate performance of the battery, improves the precipitation of metallic lithium on the negative electrode, and thus reduces safety hazards.
[0053] The electrolyte provided in the present application, through the selection of the structure of the silicon-substituted carbonate compound and the optimization of the dosage, reduces the internal rotation barrier of the silicon-substituted post-bond and increases the flexibility, so that the viscosity of the original solvent is reduced, the shuttle ability of the lithium-ion battery in the solvent is improved, and the low-temperature performance and rate performance of the lithium-ion battery can be further improved. DETAILED DESCRIPTION
[0054] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0055] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0056] As used in this application, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0057] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0058] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0059] Moreover, the technical features involved in various embodiments of the present invention can be combined with each other as long as they do not conflict with each other. The present application is further described in detail below in conjunction with specific embodiments.
[0060] Example 1
[0061] This embodiment provides an electrolyte, which includes, based on the total mass of the electrolyte, 5% of a silicon-substituted carbonate compound having a structure represented by formula (II-1), 2% of vinylene carbonate (VC), 1% of fluoroethylene carbonate (FEC), 1% of 1,3-propane sultone (PS), 0.5% of vinyl sulfate (DTD) and 0.3% of lithium difluorooxalatoborate (LiODFB), and 0.5% of a fluorophenyl ring phosphate compound having a structure represented by formula (I-1), wherein the concentration of lithium hexafluorophosphate in the electrolyte is 1.3 mol / L, and the rest is a mixed solvent;
[0062] The preparation method is as follows:
[0063] In a glove box, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 35:30:35, and then a silicon-substituted carbonate compound is added to the mixed solvent, and then lithium hexafluorophosphate is added for dissolution, and finally vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), vinyl sulfate (DTD), lithium difluorooxalatoborate (LiODFB) and fluorophenyl ring phosphate compounds are added and mixed evenly to obtain an electrolyte.
[0064] Example 2
[0065] The difference between Example 2 and Example 1 is that 1.0% of compound (I-1) is added to the electrolyte in Example 2.
[0066] Example 3
[0067] The difference between Example 3 and Example 1 is that 1.5% of compound (I-1) is added to the electrolyte in Example 3.
[0068] Example 4
[0069] The difference between Example 4 and Example 1 is that 1.0% of compound (I-2) is added to the electrolyte in Example 4.
[0070] Example 5
[0071] The difference between Example 5 and Example 1 is that 1.0% of compound (I-3) is added to the electrolyte in Example 5.
[0072] Example 6
[0073] The difference between Example 6 and Example 1 is that 1.0% of compound (I-4) is added to the electrolyte in Example 6.
[0074] Example 7
[0075] The difference between Example 7 and Example 1 is that 1.0% of compound (I-5) is added to the electrolyte in Example 7.
[0076] Example 8
[0077] The difference between Example 8 and Example 2 is that 5% of silyl carbonate compound (II-2) is added to the electrolyte in Example 8.
[0078] Example 9
[0079] The difference between Example 9 and Example 8 is that 5% of silyl carbonate compound (II-3) is added to the electrolyte in Example 9.
[0080] Example 10
[0081] The difference between Example 10 and Example 9 is that 5% of silyl carbonate compound (II-4) is added to the electrolyte in Example 10.
[0082] Embodiment 11
[0083] The difference between Example 11 and Example 2 is that 10% of the silyl carbonate compound (II-1) is added to the electrolyte in Example 11.
[0084] Example 12
[0085] The difference between Example 12 and Example 4 is that 10% of the silicon-substituted carbonate compound (II-1) is added to the electrolyte in Example 12.
[0086] Example 13
[0087] The difference between Example 13 and Example 5 is that 10% of the silicon-substituted carbonate compound (II-1) is added to the electrolyte in Example 13.
[0088] Embodiment 14
[0089] The difference between Example 14 and Example 6 is that 10% of the silicon-substituted carbonate compound (II-1) is added to the electrolyte in Example 14.
[0090] Embodiment 15
[0091] The difference between Example 15 and Example 7 is that 10% of the silyl carbonate compound (II-1) is added to the electrolyte in Example 15.
[0092] Example 16
[0093] The difference between Example 16 and Example 2 is that 10% of silicon-substituted carbonate compound (II-2) is added to the electrolyte in Example 16.
[0094] Embodiment 17
[0095] The difference between Example 17 and Example 4 is that 10% of a silicon-substituted carbonate compound (II-2) is added to the electrolyte in Example 17.
[0096] Embodiment 18
[0097] The difference between Example 18 and Example 5 is that 10% of silicon-substituted carbonate compound (II-2) is added to the electrolyte in Example 18.
[0098] Embodiment 19
[0099] The difference between Example 19 and Example 6 is that 10% of silicon-substituted carbonate compound (II-2) is added to the electrolyte in Example 19.
[0100] Embodiment 20
[0101] The difference between Example 20 and Example 7 is that 10% of a silicon-substituted carbonate compound (II-2) is added to the electrolyte in Example 20.
[0102] Embodiment 21
[0103] The difference between Example 21 and Example 2 is that 10% of silicon-substituted carbonate compound (II-3) is added to the electrolyte in Example 21.
[0104] Embodiment 22
[0105] The difference between Example 22 and Example 4 is that 10% of silicon-substituted carbonate compound (II-3) is added to the electrolyte in Example 22.
[0106] Embodiment 23
[0107] The difference between Example 23 and Example 5 is that 10% of a silicon-substituted carbonate compound (II-3) is added to the electrolyte in Example 23.
[0108] Embodiment 24
[0109] The difference between Example 24 and Example 6 is that 10% of silicon-substituted carbonate compound (II-3) is added to the electrolyte in Example 24.
[0110] Embodiment 25
[0111] The difference between Example 25 and Example 7 is that 10% of a silicon-substituted carbonate compound (II-3) is added to the electrolyte in Example 25.
[0112] Embodiment 26
[0113] The difference between Example 26 and Example 2 is that 10% of silicon-substituted carbonate compound (II-4) is added to the electrolyte in Example 26.
[0114] Embodiment 27
[0115] The difference between Example 27 and Example 4 is that 10% of a silicon-substituted carbonate compound (II-4) is added to the electrolyte in Example 27.
[0116] Embodiment 28
[0117] The difference between Example 28 and Example 5 is that 10% of a silicon-substituted carbonate compound (II-4) is added to the electrolyte in Example 28.
[0118] Embodiment 29
[0119] The difference between Example 29 and Example 6 is that 10% of silicon-substituted carbonate compound (II-4) is added to the electrolyte in Example 29.
[0120] Embodiment 30
[0121] The difference between Example 30 and Example 7 is that 10% of a silicon-substituted carbonate compound (II-4) is added to the electrolyte in Example 30.
[0122] Embodiment 31
[0123] The difference between Example 31 and Example 2 is that no silicon-substituted carbonate compound (II-1) is added to the electrolyte of Example 31.
[0124] Embodiment 32
[0125] The difference between Example 32 and Example 4 is that no silicon-substituted carbonate compound (II-1) is added to the electrolyte of Example 32.
[0126] Embodiment 33
[0127] The difference between Example 33 and Example 5 is that no silicon-substituted carbonate compound (II-1) is added to the electrolyte of Example 33.
[0128] Embodiment 34
[0129] The difference between Example 34 and Example 2 is that 2.0% of compound (Ⅰ-1) is added to the electrolyte of Example 34.
[0130] Embodiment 35
[0131] The difference between Example 35 and Example 2 is that 3.0% of compound (Ⅰ-1) is added to the electrolyte of Example 35.
[0132] Embodiment 36
[0133] This embodiment provides an electrolyte, which includes, based on the total mass of the electrolyte, 5% of a silicon-substituted carbonate compound having a structure represented by formula (II-1), 2% of vinylene carbonate (VC), 1% of fluoroethylene carbonate (FEC), 1% of 1,3-propane sultone (PS), 0.5% of vinyl sulfate (DTD) and 1% of a fluorophenyl ring phosphate compound having a structure represented by formula (I-1), wherein the concentration of lithium hexafluorophosphate in the electrolyte is 1.3 mol / L, and the rest is a mixed solvent;
[0134] The preparation method is as follows:
[0135] In a glove box, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 35:30:35, and then a silicon-substituted carbonate compound is added to the mixed solvent, and then lithium hexafluorophosphate is added for dissolution, and finally vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), vinyl sulfate (DTD) and fluorophenyl ring phosphate compounds are added and mixed evenly to obtain an electrolyte.
[0136] Comparative Example 1
[0137] This comparative example provides an electrolyte, which is different from Example 1 in that the electrolyte does not include a silyl carbonate compound having a structure represented by formula (II-1) and a fluorophenyl cyclic phosphate compound having a structure represented by formula (I-1).
[0138] Comparative Example 2
[0139] This comparative example provides an electrolyte, which is different from Example 1 in that the electrolyte does not contain a fluorinated benzene cyclic phosphate compound having a structure represented by formula (I-1).
[0140] Comparative Example 3
[0141] This comparative example provides an electrolyte, which is different from Example 8 in that the electrolyte does not include a fluorinated benzene cyclic phosphate compound having a structure represented by formula (I-1).
[0142] Comparative Example 4
[0143] This comparative example provides an electrolyte, which is different from Example 9 in that the electrolyte does not include a fluorinated benzene cyclic phosphate compound having a structure represented by formula (I-1).
[0144] Comparative Example 5
[0145] This comparative example provides an electrolyte, which is different from Example 10 in that the electrolyte does not include a fluorinated benzene cyclic phosphate compound having a structure represented by formula (I-1).
[0146] Test Case
[0147] 1. Lithium-ion battery preparation
[0148] The electrolyte provided in each embodiment and comparative example was injected into a fully dried lithium iron phosphate / graphite soft-pack battery (model GRP9068088, battery capacity 3.5Ah), and after 45°C storage, high-temperature fixture formation and secondary sealing processes, the battery performance test was carried out to obtain a lithium-ion battery.
[0149] 2. High temperature cycle performance
[0150] Under high temperature (45°C), the lithium-ion battery was charged to 3.75V at 1C constant current and constant voltage, and then discharged to 2.0V at 1C constant current. After 300 cycles of charge and discharge, the capacity retention rate after the 300th cycle was calculated according to the following formula:
[0151] Capacity retention rate (%) = 100% × discharge capacity after the 300th cycle / discharge capacity of the first cycle.
[0152] 3. Low temperature cycle performance
[0153] At low temperature (10°C), the lithium-ion battery was charged to 3.75V at 0.5C constant current and constant voltage, and then discharged to 2.0V at 1C constant current. After 50 cycles of charge and discharge, the capacity retention rate after the 50th cycle was calculated according to the following formula:
[0154] Capacity retention rate (%) = 100% × discharge capacity after the 50th cycle / discharge capacity after the first cycle.
[0155] 4. High temperature storage performance
[0156] At room temperature (25°C), the lithium-ion battery is charged and discharged at 0.5C / 1C (the discharge capacity is recorded as DC0), and then charged to 3.75V under 1C constant current and constant voltage conditions; the lithium-ion battery (100% SOC) is placed in a 60°C high temperature box for 30 days, and after being taken out, it is discharged at 1C under room temperature (the discharge capacity is recorded as DC1); then it is charged and discharged at 0.5C / 1C under room temperature (the discharge capacity is recorded as DC2), and the capacity retention rate and capacity recovery rate of the lithium-ion battery are calculated using the following formula:
[0157] Capacity retention rate (%) = 100% × DC1 / DC0; Capacity recovery rate (%) = 100% × DC2 / DC0.
[0158] 5. Electrolyte viscosity
[0159] A. Use a viscometer (BROOKFIELD DV2T viscometer) to measure the viscosity of the electrolyte and start the equipment
[0160] 1) Turn on the Brookfield Viscometer and adjust the horizontal angle so that the level bead of the instrument is in the center;
[0161] 2) Follow the instrument prompts, remove the rotor, click Next, and the device will automatically calibrate to zero until the automatic zero calibration is completed.
[0162] B. Set up viscosity test
[0163] 1) Click the rotor column, enter "0", select the rotor "ULA(0)", and click "Ok";
[0164] 2) Click the speed bar, select the speed "60RPM", and click "Ok";
[0165] 3) Click the end condition, set the time to "00:01:00", and click "Ok";
[0166] 4) Select data collection as "Single Point".
[0167] C. Viscosity test
[0168] 1) Install the ULA(0) rotor and add about 10 mL of electrolyte to cover the upper surface of the rotor;
[0169] 2) Click "Run" to finish the instrument operation and read the electrolyte viscosity reading.
[0170] 6. Lithium Separation
[0171] After the low-temperature cycle performance test, the fully charged cells were disassembled in an environment with a dew point of 40°C and the negative electrode sheets were photographed. The morphology of the negative electrode sheets of the cells corresponding to each electrolyte was recorded, and the lithium plating situation was observed.
[0172] The specific test results are shown in the table below:
[0173] Table 1
[0174]
[0175]
[0176] From the data in the above table, it can be seen that Examples 1-3 respectively add 0.5%, 1%, and 1.5% of the compound (I-1) by weight of the electrolyte. From the data in the above table, it can be seen that after the additive is introduced into the electrolyte, the low-temperature cycle and high-temperature storage performance of the obtained lithium-ion battery are significantly improved; when the amount of the additive added is less than 1%, the cycle performance tends to improve with the increase of its addition amount, and when the addition amount is ≥1.5%, the low-temperature cycle performance and high-temperature cycle performance decrease instead. It can be seen that the addition amount of this type is best when it is 0.5-1.5% (such as 1%), and too little addition will not improve the high temperature effect, and too much addition may cause the battery internal resistance to increase. This is related to the DCIR growth effect of a large number of P=O bonds on the battery.
[0177] In Example 2 and Example 11, 5% and 10% of the compound (II-1) by mass of the electrolyte were added respectively. From the data in the above table, it can be seen that after different amounts of silicon-substituted solvents were introduced into the electrolyte, the low-temperature cycle and high-temperature storage performances of the obtained lithium-ion batteries were not much different. The main difference is that the viscosity of the electrolyte tends to decrease. The main reason is that the excellent fluidity and low viscosity of the silicon-substituted solvent neutralize the viscosity of the cyclic carbonate.
[0178] Comparative Examples 2-5 add 5% of the mass of the silicon-substituted solvent compound (II-1) to the electrolyte, while Examples 1, 8, 9, and 10 add 1% of the compound (I-1) respectively on the basis of the above. It can be seen from the data in the above table that after the additive is introduced into the electrolyte, the low-temperature cycle and high-temperature storage performance of the resulting lithium-ion battery are significantly improved. Compared with the use of a single silicon-substituted solvent, the combined use of the two produces an effect of 1+1>2. It is believed that the reduction of the additive on the negative electrode to form a LiF-rich SEI film does not affect the shuttling of the silicon-substituted solvent on the surface of the negative electrode of the battery cell.
[0179] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. An electrolyte, characterized in that: It includes lithium salt, organic solvent and additives, wherein the electrolyte also includes a fluorinated benzene ring phosphate compound having a structure shown in formula (I): R1, R2, R3, and R4 independently represent at least one of halogen, substituted or unsubstituted alkyl with 1-5 carbon atoms, substituted or unsubstituted alkoxy with 1-5 carbon atoms, substituted or unsubstituted olefin with 1-5 carbon atoms, substituted or unsubstituted alkyne with 1-5 carbon atoms, cyano, isocyanate, and siloxane; or, R1 and R2 are connected to form a ring, and R3 and R4 are connected to form a ring, and the rings independently include at least one of substituted or unsubstituted carbon heterocycle and substituted or unsubstituted aromatic heterocycle; wherein the substituents in the substituted alkyl, substituted alkoxy, substituted olefin, substituted alkyne, substituted carbon heterocycle, and substituted aromatic heterocycle independently include at least one of halogen, CN, NH2, and CHO; The fluorinated benzene ring phosphate compound accounts for 0.5% to 3% of the total mass of the electrolyte.
2. The electrolyte according to claim 1, characterized in that The fluorinated benzene ring phosphate compound has any of the following structures:
3. The electrolyte according to claim 1 or 2, characterized in that The fluorinated benzene ring phosphate compound accounts for 0.5% to 1% of the total mass of the electrolyte.
4. The electrolyte according to claim 1 or 2, characterized in that The electrolyte also includes a silicon-substituted carbonate compound having a structure shown in the following formula (II): Wherein, R5, R6, R7, and R8 each independently represent at least one of halogen, substituted or unsubstituted alkyl with 1-5 carbon atoms, substituted or unsubstituted alkoxy with 1-5 carbon atoms, substituted or unsubstituted olefin with 1-5 carbon atoms, and substituted or unsubstituted alkynyl with 1-5 carbon atoms, wherein the substituents in the substituted alkyl, substituted alkoxy, substituted olefin, and substituted alkynyl independently include at least one of halogen, CN, NH2, and CHO.
5. The electrolyte according to claim 4, characterized in that The silicon-substituted carbonate compound has any of the following structures:
6. The electrolyte according to claim 4, characterized in that The silicon-substituted carbonate compound accounts for 5% to 10% of the total mass of the electrolyte.
7. The electrolyte according to claim 1 or 2, characterized in that: The concentration of the lithium salt in the electrolyte is 0.5 to 2 mol / L in terms of lithium ions.
8. The electrolyte according to claim 7, characterized in that The additive accounts for 0.1% to 15% of the total mass of the electrolyte; And / or, the concentration of the lithium salt in the electrolyte is 1 to 1.5 mol / L in terms of lithium ions.
9. A lithium ion battery, characterized in that: The electrolyte comprising the electrolyte according to any one of claims 1 to 8.
10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.